Kinetics of Texture and Colour Changes in Chicken Sausage During Superheated Steam Cooking - Abdulhameed, Asmaa A.; Yang, Tajul A.; Abdulkarim, A. A. (De Gruyter Open, 2016)
The aim of this study was to develop a kinetic model to describe the texture and colour changes of chicken sausage during superheated steam cooking. Chicken sausages were cooked at temperature ranging from 150 13200